2004
DOI: 10.1002/ajmg.b.30024
|View full text |Cite
|
Sign up to set email alerts
|

Association analysis of the DRD4 and COMT genes in methamphetamine abuse

Abstract: We analyzed two polymorphisms in genes encoding proteins of the dopamine system, the Val158Met polymorphism in the catechol-O-methyltransferase gene and the 120-bp VNTR polymorphism in the promoter of the dopamine D4 receptor gene for association with methamphetamine abuse. We used a case/control design with 416 methamphetamine abusing subjects and 435 normal controls. All subjects were Han Chinese from Taiwan. We found an excess of the high activity Val158 allele in the methamphetamine abuser group, consisten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
57
2
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(66 citation statements)
references
References 46 publications
5
57
2
2
Order By: Relevance
“…These results are in accordance with the literature [20,21,31]. But other authors have not replicated these findings [18,32,33].…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…These results are in accordance with the literature [20,21,31]. But other authors have not replicated these findings [18,32,33].…”
Section: Discussionsupporting
confidence: 85%
“…Although this polymorphism has been already studied in drug addicts [19,20,30], to our knowledge, this is the first screening to include a correlation with paranoid ideation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other evidence supporting an association of this polymorphism together with a haplotype of markers in the 5 0 end of the gene and ADHD has been reported (P 5 0.03) . Additionally, studies have reported associations of this repeat with schizophrenia (P 5 0.003) [Xing et al, 2003] and (less robustly) methamphetamine abuse (P 5 0.01) [Li et al, 2004]. Other studies have reported an association with novelty seeking in bipolar (P 5 0.01) and alcoholic families (P 5 0.006) [Rogers et al, 2004].…”
Section: Dopamine Receptor D4 (Drd4)mentioning
confidence: 95%
“…While pitfalls such as small samples and confounding (i.e., population stratification) have been blamed (Lachman, 2006), the lack of replication may also be due, in part, to differences in selection criteria for the control groups across studies, particularly with respect to the inclusion of abstainers (Buckland, 2001;Tsuang et al, 1999), i.e., individuals who never used the substance. Some studies restricted control subjects to abstainers (Gerra et al, 2004;Li et al, 2004;Liu et al, 2005;Uhl et al, 2001) or those with extremely low frequency of use (Morita et al, 2005;Xu et al, 2002). Other studies specifically included users, i.e., those exposed to the substance (Kohnke et al, 2005;Sullivan et al, 2001a) and attempted to match on level of drug use (Franke et al, 2003).…”
Section: Introductionmentioning
confidence: 99%